Determination of ptaquiloside in pteridium aquilinum (l.) Kuhn - P, Otgonsugar; Ts, Undrakhbayar; Ts, Byambajav (Mongolian Journal of Agricultural Sciences, 2018)
Bracken (Pteridium aquilinum (L. Kuhn)), use widely in the eastern and western medicine and food, has attracted researchers interest. It is related with norsesquiterpene glucoside ptaquiloside, which is carcinogen, contains in the bracken. Therefore, our aim of the study was quantitatively and qualitatively to determine ptaquiloside in the bracken and relationship between the ptaquiloside and it’s degrade or inactive way, which is “Nomkhotgol”. Nomkhotgol is a way of decreasing or inactivating toxic effect and increasing the treatment activity in raw material of drug. Ptaquiloside was present in all samples, with a minimum of 0,41ug/g in sample 1-1 (used the Nomkhotgol), with a maximum of 49.68 ug/g in spore and 10.06-32.01 ug/g in other samples. Total proteins of sample (1-1 ) were 0,01% of low compared to sample 1-2 and 0.01% of high compared to sample 5 (not spore), sample 6 (with spore). Also, total flavonoids were 1,39-5,3 times and total saponins were 1,26-53,8 times low compared to other samples. Эгэл бавран (pteridium aquilinum (l.) kuhn)-д птаквиклозидыг илрүүлсэн дүн Хураангуй: Өрнө, дорнын анагаах ухаан болон хүнсэнд хэрэглэгдэж ирсэн Эгэл бавран (Pteridium aquilinum (L.) Kuhn) нь судлаачдын сонирхлыг ихээхэн татаж ирсэн билээ. Энэ нь түүнд агуулагдах норсесквитерпений бүлгийн гликозид болох птаквиклозид нь хорт хавдар үүсгэдэг (канцероген)-тэй холбоотой юм. Тиймээс бид Эгэл баврангийн дорно дахины аргаар боловсруулалт хийсэн (номхотгол) ба хийгээгүй дээжинд птаквиклозидыг чанарын ба тоон тодорхойлолт хийж, харьцуулан судлав. Судалгааны үр дүнгээс харахад боловсруулалт хийсэн (номхотгосон) ургамлын дээжинд 0.41 мкг/г, спорлосон дээжинд хамгийн их буюу 49.68 мкг/г, бусад дээжинд 10.06-32.01 мкг/г хэмжээтэй птаквиклозид агуулагдаж байгааг тогтоолоо. Харин боловсруулалт хийсэн дээжинд (1-1) агуулагдах нийт уургийн хэмжээ боловсруулалт хийгээгүй дээжнээс (1-2) 0.01%-иар бага, споргүй (5) болон спортой (6) дээжнээс 0.0181-0.0194%-иар их байна. Мөн нийлбэр флавоноидын хэмжээ бусад дээжнийхээс 1.39-5.3, нийлбэр сапонины хэмжээ 1.26-53.8 дахин бага байлаа. Түлхүүр үг: Pterosin B, норсесквитерпений гликозид, нимгэн үеийн хроматографи, өндөр мэдрэмжит шингэний хроматографи